Protein Phosphorylation in Parasites 2013
DOI: 10.1002/9783527675401.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Kinases in Leishmaniasis

Abstract: Leishmania is an obligatorily intracellular parasite residing and replicating in mammalian macrophages as amastigotes. Once activated, macrophages destroy Leishmania amastigotes. The macrophages can be activated by stimulating CD40, a costimulatory receptor, with an agonistic antibody or a recombinant CD40-ligand. CD40-induced macrophage activation involves different kinases. CD40 signals reciprocally trigger counteractive effector functions through two mitogen-activated protein kinases: p38MAPK and ERK-1/2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The quality of the response pertains to its counteractively functioning elements. Using CD40 as a model receptor with crucial roles in diverse immune functions, we previously showed that such counteractive functions or the quality of the response-proinflammatory or antiinflammatory-are regulated by a signaling system with signal strength calibrating feedback loops (7,10). The CD40 signaling system consists of cascades of kinases in two modules: one module transmits CD40 signal through lyn and p38MAPK while the other module transmits CD40 signal through syk and ERK-1/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the response pertains to its counteractively functioning elements. Using CD40 as a model receptor with crucial roles in diverse immune functions, we previously showed that such counteractive functions or the quality of the response-proinflammatory or antiinflammatory-are regulated by a signaling system with signal strength calibrating feedback loops (7,10). The CD40 signaling system consists of cascades of kinases in two modules: one module transmits CD40 signal through lyn and p38MAPK while the other module transmits CD40 signal through syk and ERK-1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Although these reports argued that the levels of activation are dependent on the extent of phosphorylation of p38MAPK and ERK-1/2, we argue that the observed reciprocity of MAPK phosphorylation is a function of a phosphatase that dephosphorylates these MAPKs differentially, as the cycle of phosphorylation and dephosphorylation of a kinase maintains the homeostasis of cellular signaling. Indeed, CD40-induced activation of MKP-1 and MKP-3, the dual-specific phosphatases, reciprocally regulates CD40 signaling through p38MAPK and ERK-1/2 and controls the host-protective antileishmanial immune response (9,10).…”
mentioning
confidence: 99%
“…The characterisation of the divergences between the kinome of several parasites from those of their mammalian host has become a source of new targets for novel anti-infective drugs 8 , 9 . Moreover, the pharmacological role of PKis has been extended beyond the selective inhibition of PKs from the pathogen to revert changes in the protein phosphorylation pattern of the host, driven by the pathogen in order to ensure its survival inside the host 10 , 11 . Concerning the former mode of action, two different approaches have been used: first, the design of PKis for atypical kinases of the pathogen 12 which are absent in the host, and second, to exploit the often subtle differences between homologue kinases of the parasite and of the host 13 .…”
Section: Introductionmentioning
confidence: 99%